Incidence, Causes, and Timing of 30-Day Readmission following Total Hip Arthroplasty - Curtis, Gannon L.; Jawad, Michael; Samuel, Linsen T.; Higuera-Rueda, Carlos A.; Little, Bryan E.; Darwiche, Hussein L. (The Journal of Hip Surgery, 2019)
Unplanned readmissions are associated with increased financial burdens. It is important to understand why they occur and how to reduce them. This study identifies incidences, trends, causes, and timing of 30-day readmissions after total hip arthroplasty (THA). Primary THA cases from 2012 to 2016 in the American College of Surgeons National Surgical Quality Improvement Program (ACS NSQIP) database were identified (n = 122,451). Fractures (n = 3,990), nonelective surgery (n = 1,715), and bilateral THA (n = 730) were excluded, leaving 116,016 cases. Linear regression analysis determined readmission trends overtime. The readmission rate after THA from 2012 to 16 was 3.32%, which significantly decreased during this time (p = 0.022). The top five causes of readmission included musculoskeletal complications (14.8%), deep surgical site infections (SSI; 11.1%), non-SSI infections (10.8%), gastrointestinal complications (GI; 7.5%), and cardiovascular complications (CV; 7.0%). The most common cause of readmission during week 1 was non-SSI infections (13.0%), week 2 was musculoskeletal complications (16%), week 3 was deep SSI (18.4%), and week 4 was deep SSI (18.6%). Causes of readmission that significantly decreased (p < 0.05) from week 1 to 4 include CV complications, GI complications, non-SSI infections, pain, and respiratory complications. In contrast, causes that significantly increased during this time included deep SSI, prosthesis complications, superficial SSI, and wound complications. Readmissions following THA significantly declined from 2012 to 2016. The most common causes of readmission were musculoskeletal complications, deep SSI, non-SSI infections, GI complications, and CV complications. Interestingly, the most common causes of readmission changed from week to week. These findings may help to develop policies to prevent readmissions following THA.
Keywords: readmission; 30-day; arthroplasty; incidence; timing